COVID-19 induced stress among dentists affecting pediatric cooperation and alter treatment of choice - Mervat Khoury Absawi; Kholoud Fahoum; Liora Costa; Amiel A. Dror; Nicole M. Bernfeld; Daniel Oren; Shmuel Einy; Fares Kablan; Samer Srouji (Elsevier, 2022)
Objectives: To assess the effect of the COVID-19 pandemic on self-rated stress levels among dentists who treated children during the outbreak and pediatric patient cooperation during dental treatments. Methods and materials: This cross-sectional study was assessed by enrolling an online questionnaire among dental practitioners treated children during April 2020. Results: Dentists with higher COVID-19-induced distress reported a lower degree of pediatric patient cooperation during dental treatments than dentists with lower reported stress (p value < 0.01). Additional factors negatively impacting patient cooperation were degree of professional practitioner seniority in pediatric dentistry, and perceived knowledge about the COVID-19 disease infectivity and feeling protective against viral transmission with Personal Protective Equipment (PPE). Also, stress levels among dentists treating children influenced medical decisions, such as the selected treatment approach influenced by COVID-19 considerations. Conclusion: The COVID-19 pandemic has adverse effects on clinicians and pediatric patients. Educational programs should be developed to advance dental staff.